Asuhan Keperawatan Pada Tn. Y Dengan Penerapan Terapi Vokal AIUEO Terhadap Kemampuan Berbicara Pada Pasienstroke Hemoragik Di Ruang Krisan RSUD Arifin Achmad Pekanbaru - Anggraini, Feby; Kusumawati, Nila; Safitri, Yenny (Komunika : Jurnal Ilmiah Komunikasi, 2023)
One form of rehabilitation therapy for speech disorders (aphasia) is by providing speech therapy. Speech therapy is an action given to individuals who experience communication disorders, speech language disorders, and swallowing disorders. The speech therapy used in this research is vocal therapy A, I, U, E, O. AIUEO vocal therapy aims to improve speech so that it can be understood by others. The aim of the final scientific work is to analyze the vocal therapy intervention A, I, U, E, O to improve verbal communication in hemorrhagic stroke patients. The method for writing KIAN is a case study with a quasi-experimental vocal therapy intervention A, I, U, E, O carried out on hemorrhagic stroke patients with verbal communication disorders. This therapy is carried out repeatedly 2 times a day for 7 days with an administration time of 30 minutes. The results of implementing 2 times a day for 7 days the application of vocal therapy A, I, U, E, O can improve verbal communication in hemorrhagic stroke patients with an increase in the communication scale from 11 to 22. The conclusion is that there is a significant increase in the communication scale in hemorrhagic stroke patients after being given vocal therapy A,I,U,E,O. This case study was carried out on hemorrhagic stroke patients with problems with verbal communication disorders. It is hoped that future researchers can carry out in-depth case studies and apply other, more effective methods to improve verbal communication.